Diversity and host preferences of ferns and lycopods epiphytes on palm trees - Titien Ngatinem Praptosuwiryo; SUMANTO SUMANTO; RIA CAHYANINGSIH (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Praptosuwiryo TN, Sumanto, Cahyaningsih. 2019. Diversity and host preferences of ferns and lycopods epiphytes on palm trees. Biodiversitas 20: 3731-3740. Epiphytic ferns contribute importantly to the global biodiversity of tropical rain forests. However, our knowledge of the ecology of epiphytic ferns is phenomenally still limited. Most studies on the ecology, floristic and diversity of epiphytic ferns and lycopods were reported outside of Malesian region. This study aimed: (i) to figure out the diversity of ferns and lycopods on palm trees of the lowland areas by analyzing its species richness and floristic composition, and (ii) to determine the host preferences of epiphytic ferns on palm trees. Twenty-eight phorophyte species belonging to 17 genera of palm trees, growing at Bogor Botanic Gardens, were observed. Trunk of palm trees was divided into three zones (basal, middle and upper). Individual numbers for each species of epiphytic fern growing on each zone were recorded. Epiphytic fern species which were most commonly found were analyzed statistically to determine their preference for the host trees. A total of 16 species of epiphytic ferns and lycopods were recorded. The greatest richness of species occurred in Polypodiaceae (50%). Habitual true epiphyte was the predominant ecological category, representing 75 % of the species. Caryota no Becc. hosted the greatest number of ferns and lycopods 8 species) while Attalea insignis (Mart.) Drude hosted the fewest (2 species). Individual numbers of six epiphytic fern species were significantly affected by palm trees species, namely Belvisia callifolia (Christ) Copel., Pyrrosia lanceolata (L.) Farwell, Pyrrosia piloselloides (L.) M.G. Price, Davallia denticulata (Burm.) Mett., Nephrolepis biserrata (Sw.) Schott, Vittaria ensiformis Sw. Individual numbers of five epiphytic fern species were significantly affected by zone of the host plant. Nephrolepis biserrata tends to grow well in the upper zone. Pyrrosia lanceolata tends to be abundant in the middle zone. B. callifolia, D. denticulata, and V. ensiformis grow well and make dense populations in the basal zone.